2019
DOI: 10.1634/theoncologist.2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Checkpoint Inhibitor Therapy for Advanced Urothelial Cell Carcinoma at the End of Life: Insights from Real-World Practice

Abstract: Because immune checkpoint inhibitor therapies (CPI) lack the toxicities of chemotherapy, oncologists may prescribe CPI to patients at the end of life. This article describes real‐world patterns of CPI initiation near the end of life among individuals with metastatic urothelial cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 10 publications
(10 reference statements)
1
46
1
Order By: Relevance
“…However, since the initial approval of atezolizumab in 2016, ICIs have changed the treatment landscape for aUC. Because ICIs are generally better tolerated than chemotherapy, much higher use has been reported near the end of life (EOL) and among those with a poor PS despite limited data from clinical trials regarding benefit in this population. Recent accelerated FDA approval of erdafitinib for tumors harboring FGFR2/3 alterations and promising results in phase 2 trials with other targeted therapies and antibody drug conjugates, such as enfortumab‐vedotin, sacituzumab govitecan (IMMU‐132), and anti‐HER2 compounds, can further increase nonchemotherapy treatment options for aUC .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, since the initial approval of atezolizumab in 2016, ICIs have changed the treatment landscape for aUC. Because ICIs are generally better tolerated than chemotherapy, much higher use has been reported near the end of life (EOL) and among those with a poor PS despite limited data from clinical trials regarding benefit in this population. Recent accelerated FDA approval of erdafitinib for tumors harboring FGFR2/3 alterations and promising results in phase 2 trials with other targeted therapies and antibody drug conjugates, such as enfortumab‐vedotin, sacituzumab govitecan (IMMU‐132), and anti‐HER2 compounds, can further increase nonchemotherapy treatment options for aUC .…”
Section: Discussionmentioning
confidence: 99%
“…A study of ICI utilization practices with the Flatiron Health data set showed that 23% of patients with urothelial cancer were treated with ICIs in the final 30 DOL and that at least 38% of those patients had an ECOG PS ≥ 2 at the start of ICI treatment. 13 In addition, a single-institution, retrospective cohort study by Glisch et al 33 investigated ICI use (across tumor types) near the EOL and found that 27% of the patients in their cohort of 157 patients were treated with ICIs in the last 30 DOL; ICI use in the last 30 DOL was associated with lower hospice enrollment and a higher chance of dying in the hospital. In our study, only 10% had ICI initiation in the last 30 DOL; however, ICI initiation near the EOL was associated with higher odds of dying in the hospital.…”
Section: Site Of Death For Patients Receiving Icis Near the End Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…SEER and NPCR have been well established as research resources since their inception in 1973 and 1992, respectively. As the most recent of the three sources, data derived from Flatiron Health have become a research resource in the last five years (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18); therefore, it has become increasingly critical to understand their features. SEER and NPCR collect specific incident disease data points in a systematic and ordered fashion, fulfilling a public health reporting mandate justified by the public health burden of cancer as a disease.…”
Section: Introductionmentioning
confidence: 99%